Rapid and cost-effective assessment of connectivity among assemblages of Choerodon rubescens (Labridae), using laser ablation ICP-MS of sagittal otoliths - Fairclough, D.; Edmonds, J.; Lenanton, R.; Jackson, G.; Keay, I.; Crisafulli, B.; Newman, Stephen (Elsevier, 2011)
A rapid and cost-effective assessment was required to provide advice to management on the connectivity between juvenile and adult life cycle stages of Baldchin Groper Choerodon rubescens, a labrid endemic to the west coast of Australia, which has high social value, but relatively low commercial fishery importance. To minimise costs we used laser ablation ICP-MS to analyse levels of a small suite of elements (Ca, Mg, Mn, Cu, Zn, Sr, Rb, Ba and Pb) at the margin (adult phase) and core (juvenile phase) of the same otoliths of adult C. rubescens, collected at ten locations in five management zones. The elemental composition of both otolith margins and cores differed significantly among management zones and in some cases among locations within zones. Similarity of the pattern of among-zone elemental composition in otolith margins and cores indicated that, when cores are laid down, individuals have already recruited to the zones they will occupy as adults and there is no evidence of discrete juvenile nurseries. Thus, movement of juvenile or adult C. rubescens is likely to occur at relatively small spatial scales. Monitoring and management of adult stocks at the management zone level may be appropriate to sustain stocks broadly, but may not detect more localised depletion. Methods of elemental analyses are discussed and costs and benefits of this study vs an equivalent tagging study were compared. © 2011.